Effect of dietary n-3 versus n-6 polyunsaturated fatty acids on hepatic excretion of cholesterol in the hamster - F Berr; A Goetz; E Schreiber; G Paumgartner (Journal of Lipid Research, 1993)
Dietary polyunsaturated fatty acids of the n-6 and the n-3 class show differing effects on serum lipids and hepatic lipoprotein metabolism, which could be induced by alterations in hepatocellular cholesterol balance. As both fatty acid classes exert parallel effects on lipoprotein uptake and synthesis of cholesterol in the liver, we studied whether they have differing effects on the excretory pathways for cholesterol. Male Syrian hamsters were fed for 3 weeks low-cholesterol diets supplemented (9% w/w) with either saturated (coconut fat), n-6 unsaturated (safflower oil) or n-3 unsaturated fatty acids (fish oil), which shifted the serum lipid levels. N-6 unsaturated fatty acids increased both the synthesis of cholic acid (+57%; P = 0.05) and, in fistula bile, the secretion of cholesterol (+37%; P < 0.05 vs. saturated fatty acids). By contrast, n-3 unsaturated fatty acids did not enhance synthesis of cholic acid or biliary secretion of cholesterol (-30%, NS). The fatty acid pattern of biliary phospholipids was modified according to the major unsaturated fatty acids in the diet. The alterations both in phospholipid fatty acid composition and in secretory ratio of cholesterol to phospholipids and bile acids persisted during controlled secretion of taurocholic acid at increasing rates. In conclusion, hepatic excretion of cholesterol is increased on dietary n-6 unsaturated fatty acids, and low on n-3 unsaturated fatty acids. These two dietary fatty acid classes change differently the fatty acid composition of biliary phospholipids and the secretory ratio of cholesterol to phospholipids and bile acids in bile.